MOLECULAR DOCKING OF COMPOUNDS FROM Chaetomium Sp. AGAINST HUMAN ESTROGEN RECEPTOR ALPHA IN SEARCHING ANTI BREAST CANCER - Maywan Hariono; Rollando Rollando (Sanata Dharma University, 2016)
A study on molecular docking-based virtual screening has been conducted to select virtual hit of compounds, reported its existence in fungal endophytes of Chaetomium sp. as cytotoxic agent of breast cancer. The ligands were docked into Human Estrogen Receptor alpha (HERa) as the protein which regulates the breast cancer growth via estradiol-estrogen receptor binding intervention. The results showed that two compounds bearing xanthone and two compounds bearing benzonaphtyridinedione scaffolds were selected as virtual hit ligands for HERa leading to the conclusion that these compounds were good to be developed as anti breast cancer.